Optical Genome Mapping ( OGM) : Looking beyond karyotyping - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences)
Optical genome mapping (OGM) is an advanced technology that delivers a distinct view of genome structure. It presents numerous benefits compared to conventional sequencing techniques, as well as karyotyping in identifying large-scale structural variations (SVs). SVs refer to significant alterations in the structure of a genome that go beyond the changes of individual nucleotides. These variations can have substantial effects on gene function and are linked to various genetic diseases and disorders.